Synthesis of Bisheteroarylalkanes by Heteroarylboration: Development and Application of a Pyridylidene–Copper Complex. (27th March 2019) - Huang, Yuan; Brown, M. Kevin
Abstract: The development of pyridylidene‐Cu‐complexes and their application in Cu/Pd‐catalyzed heteroarylboration of alkenylheteroarenes is reported. The significance of 1, 1′‐heteroarylalkanes as building blocks for drug discovery, as well as the straightforward and modular sequence to prepare the pyridylidene‐Cu‐complexes, makes this catalyst and it applications attractive for chemical synthesis. Furthermore, chiral variants of the pyridylidene‐Cu‐complexes have been prepared and utilized in the enantioselective arylboration of E‐alkenes, further demonstrating the value and potential of this class of catalysts.